JAVA Implementation of the Batched iLab Shared Architecture - Payne, Lenard; Schulz, Mark (International Journal of Online and Biomedical Engineering (iJOE), 2013)
The MIT iLab Shared Architecture is limited currently to running on the Microsoft Windows platform. A JAVA implementation of the Batched iLab Shared Architecture has been developed that can be used on other operating systems and still interoperate with the existing Microsoft .NET web services of MITâ??s iLab ServiceBroker. The Batched iLab Shared Architecture has been revised and separates the Labserver into a LabServer that handles experiment management and a LabEquipment that handles experiment execution. The JAVA implementation provides a 3-tier code development model that allows code to be reused and to develop only the code that is specific to each experiment.